CFD-DEM modeling of turbidity current propagation in channels with two different topographic configurations - Lu, Yang; Liu, Xiaolei; Sun, Junkai; Xie, Xiaotian; Li, Dongyang; Guo, Xingsen (Frontiers in Marine Science, 2023)
Submarine turbidity currents are a special type of sediment gravity flow responsible for turbidite deposits, attracting great interests from scientists and engineers in marine and petroleum geology. This paper presents a fully coupled computational fluid (CFD) and discrete element method (DEM) model to quantitatively analyze the turbidity current propagation in channels with two different topographic configurations. An appropriate drag force model is first incorporated in the CFD-DEM scheme, and two benchmark cases, including a single-particle sedimentation case and an immersed granular collapse case, are conducted to verify the accuracy of the developed CFD-DEM model. The model is then employed to investigate the fluid and particle dynamics of turbidity currents flowing over a flat bed (FB) and an obstacle-placed bed (OPB). The results indicate that the front position of turbidity current in the FB case is well consistent with the classic lock-exchange experiment. There are only slight variations in flow field developments between the FB and OPB cases, and thus further analysis is given using the results of the DEM module. The DEM results show that the presence of the obstacle can clearly diminish the inter-particle collisions and the particle kinetic energy, weaken the particle-fluid interactions, and further make more sediment particles settle in front of the obstacle. We show that our models enable reproducing the typical process of turbidity current propagation, and further can provide more valuable insights in understanding the turbidite-related geological phenomena from the point of view of particulate flow.